Elena Kagan Can't Say That: The Sorry State of Public Discourse Regarding Constitutional Interpretation - Neil J. Kinkopf (Washington University Law Review, 2010)
Written in the form of a fictional memo by Counsel to the President, Ray Politik, this commentary offers a reply to a fictional opening statement for Justice Kagan’s confirmation hearing. The proposal argues that Justice Kagan’s statement is strategically misguided and should not be understood as a “teaching moment”. The commentary argues that conservatives have succeeded in cementing the idea that there are two types of judges: the liberal, activist judge and the conservative judge. Finally, the hypothetical statement suggests that Justice Kagan’s proposed statement would brand her as a judicial activist, casting into doubt her prospects for confirmation. The reply argues that Justice Kagan’s statements would be inconsistent with the administration’s policy. Finally, the memo suggests that the President should promote a progressive constitutional agenda through a grassroots constituency as opposed to allowing Justice Kagan to proceed with her remarks.
Keywords: Judges – Selection & amp; appointment; Constitutional law; Kagan; Elena; 1960-